Pengaruh Peran Kepala Sekolah, Motivasi Kerja, dan Lingkungan Kerja Terhadap Kinerja Guru Sekolah Dasar di Kecamatan Kradenan Kabupaten Blora - Rulie Saraswati; Ngurah Ayu Nyoman Murniati; Widya Kusumaningsih (Departement of Mathematics Education, 2023)
The objectives of this study are: (1) knowing the magnitude of the influence of the principal's role on teacher performance. (2) knowing the magnitude of the influence of teacher work motivation on teacher performance. (3) knowing the magnitude of the influence of the teacher's work environment on teacher performance. (4) knowing the magnitude of the influence of the role of the principal, work motivation, and work environment on the performance of elementary school teachers in Kradenan District, Blora Regency. This study used a quantitative approach. The study population was 213 teachers spread across 29 schools with a sample of 139 teachers selected by proportional random sampling to analyze validity, reliability, prerequisites, and hypothesis test data using the SPSS for Windows 25 program. The results showed (1) the magnitude of the influence of the role of the head on teacher performance by 4.6%. (2) the magnitude of the influence of work motivation on teacher performance by 12.7%. (3) the magnitude of the influence of the work environment on teacher performance by 68%. (4) the magnitude of the influence of the role of the principal, work motivation, and work environment together on teacher performance by 78.9%. The conclusion of the study showed (1) there was an influence of the role of the head on teacher performance and found deficiencies in the role of the principal as a supervisor of 0.622. (2) There was an effect of work motivation on teacher performance and a deficiency was found in work motivation in intrinsic motivation of 0.763. (3) There is an influence of the work environment on teacher performance and deficiencies are found in the work environment in the non-physical environment of 0.739. (4) There is an influence on the role of the principal, work motivation, and work environment together on teacher performance.